Biomechanical Evaluation of Pediatric Anterior Cruciate Ligament (ACL) Reconstruction Techniques With and Without the Anterolateral Ligament (ALL). Issue 1 (January 2020) - Trentacosta, Natasha; Pace, James L.; Metzger, Melodie; Michalski, Max; Nelson, Trevor; Polakof, Landon; Mandelbaum, Bert
Abstract : Background: Two popular physeal-sparing procedures used in the management of anterior cruciate ligament (ACL) injuries in skeletally immature patients are the iliotibial band (ITB) ACL reconstruction (ACLR) and the all-epiphyseal (AE) ACLR. Although there has been concern for overconstraint of the lateral compartment of the knee with the ITB ACLR technique, rotational stability, as provided by the anterolateral ligament (ALL) and ACL, has not been assessed in the setting of pediatric ACLR techniques. Our hypothesis is that the ITB ACLR and AE ACLR with ALL reconstruction (ALLR) will best replicate the biomechanical profile of the intact ACL that is lost with transection of the ACL and ALL. Methods: Eight cadaveric legs were statically loaded with an anterior drawer force and varus, valgus, internal and external rotational moments at 0, 30, 60, and 90 degrees of flexion. Displacement and rotation were recorded in the following conditions: intact ACL/intact ALL, ACL-deficient/intact ALL, ITB ACLR/intact ALL, ITB ACLR/ALL-deficient, ACL-deficient/ALL-deficient, AE ACLR/ALL-deficient, AE ACLR/ALLR. Results: Both ACLR techniques reduced anterior tibial translation from the ACL-deficient state, but neither restored it to the intact state ( P <0.05), except in full extension. ALL deficiency increased anterior tibial translation in the ACL-deficient state ( P <0.05). In rotational testing, no significant increase was seen with transection of the ACL, but the ACL-deficient/ALL-deficient state had a significant increase in internal rotation ( P <0.05). This was significantly restored to the intact state at most flexion angles with the ITB ACLR without rotational overconstraint of the lateral compartment. The AE ACLR/ALL-deficient state and AE ACLR/ALLR improved rotational stability at lower flexion angles, but not at 60 and 90 degrees. There were no significant changes in varus/valgus moments. Conclusions: In this model, the ITB ACLR provided the superior biomechanical profile between our tested reconstructions. It best corrected both AP and rotatory stability without overconstraining the knee. The AE ACLR and AE ACLR/ALLR improved both parameters but not at all flexion angles and not as robustly. ACL deficiency in the knee increased anterior tibial translation, but did not affect rotatory stability. ALL deficiency in the knee increased anterior displacement and rotational moments in the ACL-deficient state. Clinical Relevance: Cadaveric Laboratory Study. The ITB ACLR seems to be the biomechanically superior pediatric ACLR technique to regain translational and rotational stability.